(3GdLhgQ GdaQjO aj JGQjN eOjfI RHjOs - (3eMeO Hf eMeO Hf efUhQ , GHf CSjQs ((3efUhQ Hf SdjeGf s)
(3ChdgG (B:s
(3hHYO , abO SCdfi ef dGJSYfi eNGdaJg Cf CVY dg JGQjNkG ai fTCI eOjfI RHjO hef HfGgG hCSSgG hMcegG ef GdhdGI hGdbVGI s
(3BNQgG (B:s
(3hde jfUdM CeQ GdCTQa Edi SdN QeVGf ef SfI NeS hCQHYjf (B( (3HYO GdKeGfi eFI (B) (3aJhai SGHY ThGd HJYR hCbje HYOg GHf Yeg jhSa GdeXaQ Hf YeQ Hf GdCTQa hUGQJ JYeQ MjfG , hJNQHgG GdYQH MjfkG , Edi jhefG gPG hgPG BNQ eG CQOfG EjQGOg s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag ai fUa TgQ LeGOi GdBNQI SfI (B950 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs